2009
DOI: 10.1144/0016-76492008-128
|View full text |Cite
|
Sign up to set email alerts
|

Radiolarian age constraints on Mesotethyan ocean evolution, and their implications for development of the Bangong–Nujiang suture, Tibet

Abstract: Radiolarian discoveries indicate that deep-marine conditions prevailed in central Tibet from the early Middle Jurassic until well into the Early Cretaceous (late Hauterivian-early Aptian; 131-121 Ma) and help to constrain the temporal extent of oceanic conditions along the Bangong-Nujiang suture. These new fossils occur in chert or siliceous mudstone blocks associated with the Lagkor Tso ophiolitic mélange. Basin inversion associated with closure of Mesotethys between the Qiangtang and Lhasa terranes was accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 34 publications
2
68
0
Order By: Relevance
“…The group consists of dark shales, siltstones, fine-to medium-grained sandstones with olistoliths, limestone lenses and quartzite. The whole sequence of sandy foreshore or shore facies sediments is possibly related to the earliest stages of basin subsidence in the southern Qiangtang realm during Early Jurassic extension (Duan et al, 2009;Schneider et al, 2003) and Meso-Tethys formation (Baxter et al, 2009). Tertiary (possible even Late Cretaceous) to recent terrestrial sediments, mostly conglomerates, cover the area in scattered, usually fault-bounded basins (Kapp et al, 2005).…”
Section: Post-collision Stratigraphy and Lithologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The group consists of dark shales, siltstones, fine-to medium-grained sandstones with olistoliths, limestone lenses and quartzite. The whole sequence of sandy foreshore or shore facies sediments is possibly related to the earliest stages of basin subsidence in the southern Qiangtang realm during Early Jurassic extension (Duan et al, 2009;Schneider et al, 2003) and Meso-Tethys formation (Baxter et al, 2009). Tertiary (possible even Late Cretaceous) to recent terrestrial sediments, mostly conglomerates, cover the area in scattered, usually fault-bounded basins (Kapp et al, 2005).…”
Section: Post-collision Stratigraphy and Lithologiesmentioning
confidence: 99%
“…Jurassic the deep-water flysch sediments (J 1−2 s) cover all the older units in the southern SQT. These are thought to represent the opening of the Bangong-Nujiang suture zone (Schneider et al, 2003;Baxter et al, 2009). It is not known whether Jurassic sediments once covered the whole Qiangtang terrane or they were never deposited there.…”
Section: Jurassic (200-170 Ma)mentioning
confidence: 99%
“…Ninomiya et al [15,17] suggested the high correlation of the detected ultramafic rocks using ASTER-TIR data with the ones described in the published ophiolite map along the middle Yarlung Zangbo river [44] for the local area south of Xigaze (indicated in Figure 8), but this study suggests the agreement within the entire region of the map. Likewise, the good agreement in the mapping results for the ultramafic rocks of Yongzhu-Guomangco section [39,40], Dong Tso section [41] and Lagkor Tso section [41,42] is suggested.…”
Section: Geological Interpretation On the Resultsmentioning
confidence: 71%
“…The most important geological features targeted in this study include the ophiolite belts appearing at the surface along the sutures of the blocks, the quartzose and carbonite sedimentary rocks deposited as the accretion wedges associated with the subduction of the oceanic plate beneath the continental plate, the granitic rocks intruded with the island arc geological setting, and the distributions of the sulfate layers as the geological evidences of the neo-Tethys environment. The field geological studies so far (e.g., [36][37][38][39][40][41][42][43]) have revealed the distribution of the target lithological features at some limited local areas in the Tibetan Plateau. However, these terranes and suture zones are poorly characterized in central Tibet, with a >1000-km-long and up to 500-km-wide tectonic belt, where the field geological surveys have not yet accomplished well for the most part of the region because this area is remote and inaccessible (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…This understanding could provide critical background information for interpreting the origin and emplacement mechanism of various types of ophiolites reported from the BNSZ, because previous studies were mostly petrology-and geochronology-oriented [18][19][20][21][22][23].…”
Section: Mappable Features Of the Mg And Tectonic Implicationsmentioning
confidence: 99%